Respuesta :
12x^2 - 11y^2 - 13x - (5x^2 - 14y^2 - 9x) =
12x^2 - 11y^2 - 13x - 5x^2 + 14y^2 + 9x =
7x^2 + 3y^2 - 4x <==
12x^2 - 11y^2 - 13x - 5x^2 + 14y^2 + 9x =
7x^2 + 3y^2 - 4x <==
Therefore, the difference of the polynomial [tex](12x^2-11y^2-13x)-(5x^2-14y^2-9x)[/tex] is [tex]7x^2+3y^2-4x[/tex]
The difference polynomial is:
[tex](12x^2-11y^2-13x)-(5x^2-14y^2-9x)[/tex]
Expand the expression using the distributive rule
[tex]12x^2-11y^2-13x-5x^2+14y^2+9x[/tex]
Collect like terms
[tex]12x^2-5x^2-11y^2+14y^2-13x+9x\\[/tex]
Simplify the expression by carrying out necessary addition and subtraction of like terms
[tex]7x^2+3y^2-4x[/tex]
Therefore, the difference of the polynomial [tex](12x^2-11y^2-13x)-(5x^2-14y^2-9x)[/tex] is [tex]7x^2+3y^2-4x[/tex]
Learn more here: https://brainly.com/question/1000323